2008
DOI: 10.1089/acm.2008.0006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Group Music Intervention on Depression, Anxiety, and Relationships in Psychiatric Patients: A Pilot Study

Abstract: These findings suggest that music can improve depression, anxiety, and relationships in psychiatric patients. However, we cannot elucidate the nonspecific effects. Furthermore, objective and replicable measures are required from a randomized controlled trial with a larger sample size and an active comparable control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 28 publications
1
51
0
13
Order By: Relevance
“…Jeong, Lee, and Park (2005) found dance reduced symptoms of somatization, depression, anxiety, hostility, obsessive-compulsions, and psychosis in adolescents, while a study regarding music intervention found improvement in adults' depression and anxiety symptoms (Choi, Lee, & Lim, 2008). Empirical evidence in the area of arts programming remains, for all intensive purposes, unrefined and based on small samples and mainly qualitative methods.…”
Section: Cultural Arts Programsmentioning
confidence: 99%
“…Jeong, Lee, and Park (2005) found dance reduced symptoms of somatization, depression, anxiety, hostility, obsessive-compulsions, and psychosis in adolescents, while a study regarding music intervention found improvement in adults' depression and anxiety symptoms (Choi, Lee, & Lim, 2008). Empirical evidence in the area of arts programming remains, for all intensive purposes, unrefined and based on small samples and mainly qualitative methods.…”
Section: Cultural Arts Programsmentioning
confidence: 99%
“…Hitherto unexplored empirically, Crawford et al’s (2013) notion of mutual recovery foregrounds interventions based in communities and facilitated by creative practices, which may provide spaces of trust and empathy. Indeed, joining the literature reviewed above centred on music, creative practice with different art forms has shown promising results in alleviating symptoms across a wide spectrum of conditions (Choi, Lee, & Lim, 2008; Ritter & Low, 1996) and has also proven effective in reducing professional burnout among physicians, clinicians, and mental health workers (Brooks, Bradt, Eyre, Hunt, & Dileo, 2010; Logid, 2011). However, research on creative practices within clinical settings has typically targeted alleviation of symptoms and reduction of ill-being rather than an in-depth assessment of psychological resources and positive functioning, failing to integrate the recent conceptualizations of well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong, Hong, Lee, and Park (2005) found dance reduced symptoms of somatization, depression, anxiety, hostility, obsessive-compulsions, and psychosis in adolescents, whereas, a study regarding music intervention found a reduction in adults' depression and anxiety symptoms (Choi, Lee, & Lim, 2008). Empirical evidence in the area of arts programming remains unrefined and based on small samples and mainly qualitative methods.…”
Section: Cultural Arts Programsmentioning
confidence: 99%